CDK5 Inhibition Abrogates TNBC Stem‐Cell Property and Enhances Anti‐PD‐1 Therapy. Issue 22 (15th October 2020) - Bei, Yuncheng; Cheng, Nan; Chen, Ting; Shu, Yuxin; Yang, Ye; Yang, Nanfei; Zhou, Xinyu; Liu, Baorui; Wei, Jia; Liu, Qin; Zheng, Wei; Zhang, Wenlong; et al.
Abstract: Triple‐negative breast cancer (TNBC) is the most aggressive subtype of breast cancer, in which the higher frequency of cancer stem cells (CSCs) correlates with the poor clinical outcome. An aberrant activation of CDK5 is found to associate with TNBC progression closely. CDK5 mediates PPAR γ phosphorylation at its Ser 273, which induces CD44 isoform switching from CD44s to CD44v, resulting in an increase of stemness of TNBC cells. Blocking CDK5/pho‐PPAR γ significantly reduces CD44v+ BCSCs population in tumor tissues, thus abrogating metastatic progression in TNBC mouse model. Strikingly, diminishing stemness transformation reverses immunosuppressive microenvironment and enhances anti‐PD‐1 therapeutic efficacy on TNBC. Mechanistically, CDK5 switches the E3 ubiquitin ligase activity of PPAR γ and directly protects ESRP1 from a ubiquitin‐dependent proteolysis. This finding firstly indicates that CDK5 blockade can be a potent strategy to diminish stemness transformation and increase the response to PD‐1 blockade in TNBC therapy. Abstract : Cancer stem cells (CSCs) promote triple‐negative breast cancer (TNBC) metastasis and therapeutic resistance, including immunotherapy. Aberrant activation of CDK5 promotes TNBC progression by triggering stemness transformation. Mechanistically, CDK5 switches the non‐canonical E3 ubiquitin ligase activity of PPARγ and protects ESRP1 from a ubiquitin‐dependent proteolysis, which controls CD44v generation. Pharmacological interruption of CDK5 reverses immunosuppressive tumor microenvironment, and enhances anti‐PD‐1 curative effects.